The Impact of Criteria and Flexibility in Nepal’s Rebel-Military Integration Program - Rana, Pranaya SJB (Unity Journal, 2022)
The integration of rebel combatants into regular forces is often a political negation for power. Several examples from the past show how such pursuits have brought about mutinies and communal violence and pushed the countries back to instability. Current literatures do not provide success stories from which crucial elements of rebel-military programs can be extracted for implementation in future programs. The thesis statement presented by the study is that conflicting parties need to invent options for mutual gain, which can be achieved using flexibility and standard criteria when all other means to achieve an agreement fail. In this regard, Nepal’s rebel-military integration process presents a unique case where former Maoist militias were integrated into the Nepali Army as individuals and after fulfilling the toned-down institutional criteria requirements. Using a qualitative design, the study of the rebel-military integration program in Nepal identified the areas within the program that adopted adequate flexibility and criteria fulfillment, and explored how those potentially led to the successful integration of ex-Maoist combatants into the Nepali Army. In order to analyze this information, secondary data such as the Interim Constitution of Nepal, 2007, the Comprehensive Peace Accord (CPA), 2006, integration program documents, journal and news articles, and organizational reports were reviewed. For the cross-validation of information, Key Personnel Interviews were conducted with program executives and Nepali Army representative, and Focus Group Discussions were conducted with regular as well Signposting in abstract and in paragraphs in the paper: It is a good idea to give a structural overview of your key arguments in the paper, for example, Part I deals with… Part II deals with.. The data analysis involved a qualitative exploratory approach in order to analyze the causal variables as discussed in the preceding research design section. The different sources of data allowed data-triangulation in order to better explore which elements of the program applied criteria and flexibility and to what degree, as well as how they impacted the integration process. The details are discussed in the subsequent sections-